Pelatihan Pemberian Makanan Tambahan dalam Pencegahan Stunting melalui Edukasi Cara Produksi Pangan Olahan yang Baik (CPPOB) - Rizki Rismawati; Siska Aula Alfianti; Iraudatul Hasanah; Syahroni Riskiyono; Danu Indra Wardhana; Trias Setyowati (Indonesian Journal Publisher, 2024)
Stunting is a common nutritional problem caused by various risk factors and is considered a chronic nutritional problem because it occurs over a short period of time. Several farmers in Maesan District, especially in Sumberanyar Village, grow various types of food crops, including dragon fruit, which is rarely used for making food. processed. For this reason, training and education on the use of local materials is carried out with a community empowerment approach. This activity aims to spread knowledge about nutrition and equip mothers with young children and cadres with skills in providing additional feeding (PMT) based on local food, namely dragon fruit pudding. Participants consisted of 18 people, including mothers of toddlers and Posyandu cadres, which was held at the Sumberanyar village hall. This community service consists of two activities, namely CPPOB education and training. It can be seen from the pretest results that 61% of posyandu cadres and mothers of toddlers had a good level of knowledge and 39% had sufficient abilities before participating in training activities. Furthermore, the posttest results after carrying out training in providing additional food in preventing stunting through education on Good Processed Food Production Methods (CPPOB) showed that the number of posyandu cadres and mothers of toddlers who had a good level of knowledge increased to 89% and the level of sufficient knowledge became 11%. The pretest and posttest results show that on average the training participants experienced an increase in knowledge about CPPOB. Research and community service to utilize local ingredients as a solution to nutritional problems through a community empowerment approach. And it can increase the skills of posyandu cadres and mothers of toddlers in preparing additional feeding (PMT) based on local food, namely dragon fruit pudding.